Comparison of breeding system costs for estrus-synchronization protocols plus artificial insemination versus natural service - Johnson, Sandra K.; Fogleman, S.L.; Jones, R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Breeding system costs were estimated for natural service and various estrous synchronization plus artificial insemination (AI) systems. Cost per pregnancy was lower for natural service than AI; however, for the large herd size the difference was small for some synchronization systems examined. When the value of an AI-sired calf at weaning was included as $25 greater than a natural service sired calf, several synchronization systems had lower breakeven prices than natural service. Assuming skilled labor could be obtained, systems that involved more heat detection time were more profitable than strict timed insemination systems. Producers that can obtain greater returns from AI-sired calves will find synchronization of estrus and AI valuable tools to increase profitability of their operation.
Keywords: Beef; estrus-synchronization protocols; Artificial insemination versus natural service